2016
DOI: 10.1039/c6fo00105j
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and faecal microbiota: a transversal study

Abstract: Despite the existing evidence on the impact of olive oil and red wine on the intestinal microbiota, the effect of the global Mediterranean Diet (MD) has not been sufficiently studied. We explored the association between the adherence to a Mediterranean dietary pattern, and its components, with faecal microbiota in a cohort of adults with non-declared pathology. This transversal study involved 31 adults without a previous diagnosis of cancer, autoimmune or digestive diseases. Based on the data obtained by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 58 publications
10
111
1
2
Order By: Relevance
“…Regarding the well-documented geographical and ethnic variation of gut microbial composition in humans (34) , similar scientific efforts may contribute to validation of the robustness of the proposed microbial indicators of metabolic health and inflammation. Moreover, the influence of the Mediterranean diet in gut microbial ecology is currently revealed (12)(13)(14)(15)18,19) , and this scientific field is open to further investigation. Thus, our findings indicate that a high adherence to the Mediterranean diet was characterised by lower E. coli counts and a subsequently higher culture-based bifidobacteria:E. coli ratio, increased levels and prevalence of C. albicans, greater molar ratio of acetate, higher defaecation frequency and a more pronounced gastrointestinal symptomatology compared with the low tertile.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the well-documented geographical and ethnic variation of gut microbial composition in humans (34) , similar scientific efforts may contribute to validation of the robustness of the proposed microbial indicators of metabolic health and inflammation. Moreover, the influence of the Mediterranean diet in gut microbial ecology is currently revealed (12)(13)(14)(15)18,19) , and this scientific field is open to further investigation. Thus, our findings indicate that a high adherence to the Mediterranean diet was characterised by lower E. coli counts and a subsequently higher culture-based bifidobacteria:E. coli ratio, increased levels and prevalence of C. albicans, greater molar ratio of acetate, higher defaecation frequency and a more pronounced gastrointestinal symptomatology compared with the low tertile.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is known that MD consumption leads to gut microbiome alterations; however, the magnitude to which these alterations occur may be potentially impacted by multiple factors such as the study duration, host age and lifestyle habits, specific disease predisposition or severity, level of dietary adherence, etc. which otherwise remain to be explicated and hence would be prerequisite to pinpoint the factors contributing to the outcome of MD on gut microbiome and deliver conclusive data on the role of gut microbiome in MD's beneficial health outcomes 124,125 . As a result, according to the existing literature, the examination of gut microbial composition could not be endorsed as a stand-alone tool for the health effects of MD.…”
Section: Non-human Primates (Nhps): An Ideal Model To Elucidate Diet-mentioning
confidence: 99%
“…Another study conducted in patients from the CORDIOPREV study has shown that consumption of a Mediterranean diet or a low-fat diet might partially restore the gut microbiome dysbiosis in obese patients with metabolic syndrome [117]. Positive associations between higher adherence to an MD diet and increased levels of the butyrate-producing species-Faecalibacterium prausnitzii and Clostridium cluster XIVa-were observed by Gutiérrez-Díaz et al [118]. Additionally, they detected that lower adherence to the MD was linked with higher urinary trimethylamine N-oxide (TMAO) levels.…”
Section: Mediterranean Diet (Md) and Gut Microbiotamentioning
confidence: 92%